Psychotherapeutic Intervention for Adults With Acquired Brain Injury: A Case Study Using BackUp - Thøgersen, Cecilie Marie S.; Glintborg, Chalotte; Hansen, Tia G. B.; Trettvik, Johan (Frontiers in Rehabilitation Sciences, 2022)
A moderate-to-severe acquired brain injury (ABI) can have tremendous lifelong consequences for ABI-survivors and their families. Despite rehabilitation practice since the 1980s aspiring to a dynamic, coherent and holistic approach, the psychological dimension still seems to be a challenge and research has revealed persisting psychosocial impairments after ABI. Therefore, we developed BackUp©, a manual based short term psychological intervention for adults with ABI. This study explores the effect of the intervention though a small feasibility study, employing a multiple baseline single case design. One client received the intervention. Self-report measures were collected, and a semi structured interview was conducted. While results from pre, post and follow-up measures do not show clear positive results, the interview reveals positive experiences and the participant reported achieving his therapy goal. This case study provides support for a psychological intervention to support the psychological rehabilitation after an ABI.